Pembelajaran Berkarakteristik Inovatif Abad 21 pada Materi Program Linear dengan Model Pembelajaran Kooperatif di Man 1 Tegal - Tholchah Kais, Muchammad (Universitas Pancasakti Tegal, 2022)
This study aims to develop 21st century innovative learning characteristics in linear programming based on cooperative learning models in class XI IPA MAN 1 Tegal. This research is a development research. Data were collected using observation sheets, and analysis of the learning design of 3 learning method models on linear programming material, namely the problem based learning model, the discovery learning model, and the cooperative learning model. The research subject is class XI MAN 1 Tegal. The results of the research analysis of learning tools state that the cooperative learning method in linear programming material has many weaknesses including not having 21st century innovative characteristics. To cover and perfect these weaknesses there are learning methods that can be alternatives in the learning process, namely problem based learning learning models and discovery learning models. learning. Problem based learning learning methods and discovery learning models can cover the shortcomings of cooperative learning methods this is because education in the 21st century is related to new problems that exist in the real world. The PBM approach is related to the use of intelligence from within individuals who are in a group of people, or the environment to solve problems that are meaningful, relevant, and contextual.